Book Classification Application Using Dewey Decimal Classification Method (DDC) Case Study Library SMAN 4 Kaur - mardianto Rian (Penerbit Jurnal Indonesia, 2021)
SMAN 4 Kaur library has not used a computerized system in providing services to visitors or students, especially in classifying existing book titles. The purpose of the research is to make a book classification application so that it can facilitate library users or managers. Where so far the book classification at SMAN 4 Kaur is still manually or has not used a system so that in its implementation it is difficult for library managers. With the construction of this application, it can help the SMAN 4 Kaur library in overcoming the process of searching for book data or book classification can run well..